PELATIHAN PEMASARAN : UPAYA PENINGKATAN PEMASARAN DAN NILAI MEREK (BRAND VALUE) KLASTER BATIK LAWEYAN MELALUI PENERAPAN PROGRAM BRANDING HERITAGE - TULUS HARYONO; TETUKO RAWIDYO PUTRO; CATUR SUGIARTO; PRAM SURYANADI; RETNO TANDING; SURYANDARI SURYANDARI; HARYANTO HARYANTO; CHRISTIYANINGSIH BUDIWATI (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2019)
The introduction of the concept of brand heritage in the Batik Industry in Kampung Batik Laweyan is intended to help local batik entrepreneurs in Kampung Batik Laweyan to maintain and preserve the uniqueness of their experiences and history, especially the Laweyan Batik tradition. Marketing training activities by introducing the concept of Brand Heritage are intended not only to raise awareness of the importance of strengthening brand identity through the concept of Brand Heritage but also to preserve Cultural Heritage.The Laweyan Batik Industry has existed even before Surakarta as the capital of the Mataram kingdom of Surakarta where most of the residents of the Laweyan area have been batik craftsmen since ancient times. Laweyan batik motifs are very diverse and are well known in the community. This community service activity involves batik entrepreneurs in the Laweyan batik village as well as employees who work at Batik Gress Tenan, Laweyan. Employees and employees who work at Batik Gress Tenan are given insight and understanding of the importance of the company and employees in maintaining the Brand Heritage of its products and maintaining the Cultural Heritage of Kampung Batik Laweyan so that it remains attractive and a strong identity to continue to exist and develop. Keywords: Brand Heritage, Cultural Heritage, Tradition, History.